Poor Peasant Condition and Its Prevention Effort - Warto Warto (Jurnal Penelitian Kesejahteraan Sosial, 2015)
This research is done to reveal economic, social, and cultural of poor peasant community, also to reveal the causal factors of poverty in Bantul Regency rural area and its strategy to prevent. The research takes place in Dlingo and Pajangan district that based on the consideration the area inhabitated by poor peasants. Data are gathered through guided interview, observation, documentary analyses, and analyzed through qualitative-descriptive technique. The result shows that the poverty is not just because of economic aspect, but cultural and social aspect of local community. The prevention effort needs strategy, some of those are coordinated program implementation from its competent parties, not just a responsible of local government, but needs commitment of corporation, non-government organization commited to poverty, and the community.